2018
DOI: 10.18388/abp.2018_2602
|View full text |Cite
|
Sign up to set email alerts
|

The favourable effect of catechin in electrochemotherapy in human pancreatic cancer cells

Abstract: Until recently, green tea polyphenols were considered strong antioxidants. However, the latest reports have revealed that bioflavonoids can play a multiple role in anticancer therapy, including the inhibition of cell proliferation and generation of the oxidative stress in a dose-dependent manner. The presented research was designed to examine the potential of the green tea (±)-catechin as a reinforcement of the electrochemotherapy (ECT) with cisplatin in pancreatic cancer in vitro. The study was performed on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…In agreement with this, our results showed that PTE triggered cell cycle arrest and apoptosis-and autophagy-mediated cytotoxicity and inhibited MDR1 expression by regulating the RAGE/PI3K/Akt axis. Although several natural compounds are used in combined therapies against pancreatic cancer such as catechins, resveratrol, and curcumin [38][39][40]. However, few available publications showed that natural compounds directly target MDR1 expression and promote chemosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this, our results showed that PTE triggered cell cycle arrest and apoptosis-and autophagy-mediated cytotoxicity and inhibited MDR1 expression by regulating the RAGE/PI3K/Akt axis. Although several natural compounds are used in combined therapies against pancreatic cancer such as catechins, resveratrol, and curcumin [38][39][40]. However, few available publications showed that natural compounds directly target MDR1 expression and promote chemosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Among many compounds tested, that is, doxorubicin, 36 ruthenium (III) compound, 37 5-fluorouracil, 38 phthalocyanines, 39 photofrin, 40 curcumin, 41 the trans-platinum analogue trans-[PtCl 2 (3-hmpy) 2 ], 42 oxaliplatin, 43 betulinic acid, 44,45 oat b-glucan, 46 cyanine IR-775, 47 catechin, 48 and sodium decahydrodecaborate, 49 only calcium electroporation was extensively studied. [50][51][52][53][54][55][56][57][58] Calcium electroporation effectively causes tumor necrosis, leaving the normal tissue less affected, making it a very promising compound for further clinical evaluation as it does not belong to the antineoplastic drugs, thus precautions related to antineoplastic drugs regarding storage, handling, disposal, and toxicity and mutagenicity are not an issue for calcium electroporation.…”
Section: Recent Advances In Electrochemotherapy 205mentioning
confidence: 99%
“…Catechin has good antitumor effects against gastric cancer, cervical cancer, pancreatic cancer, and lung cancer. However, two of its isomers have different functions [49][50][51][52]. The four isomers of catechin are (+)-catechin, (-)-catechin, (+)-epicatechin, and (-)-epicatechin.…”
Section: Discussionmentioning
confidence: 99%